(untitled) (Forum Penelitian Agro Ekonomi, 2019)
Massive land grabbing is a global phenomenon that takes place widely by involving cross-country and continental actors. However, this approach to agricultural development with this pattern is less in line with agrarian reform, because it produces inequality, conflict, and marginalization of small farmers. Various studies report the massive land grabbing especially in African countries, Latin America and also Asia. Until now, the phenomenon of land grabbing that has such serious impacts is not openly discussed by academics, and is often covered as an inter-state investment dynamic. This paper is a scientific review derived from various studies and reports, which are constructed into land grabbing character, its causal factors, the resulting impacts, and the urgency of solutions to suppress its spread. The results of the study show that in Indonesia this is also the case, and has begun to show the impacts that are less in line with the vision and mission of national agricultural development, especially the threat to the achievement of food security and farmers’ welfare. In the future, the phenomenon of land grabbing should be used as an open agenda and find solutions by integrating with agrarian reform planning. Abstrak Akuisisi lahan secara besar-besaran merupakan sebuah fenomena global yang berlangsung secara luas dengan melibatkan aktor lintas negara dan benua. Namun demikian, pendekatan pembangunan pertanian dengan pola ini kurang sejalan dengan reforma agraria, karena menghasilkan ketimpangan, konflik, serta peminggiran petani kecil. Beragam studi melaporkan masifnya akuisisi lahan terutama di negara-negara Afrika, Amerika Latin dan juga Asia. Sampai saat ini, fenomena akuisisi lahan yang memiliki dampak serius tersebut tidak dibicarakan secara terbuka oleh kalangan akademisi, dan seringkali ditutupi sebagai sebuah dinamika investasi antar negara belaka. Tulisan ini merupakan sebuah review ilmiah yang berasal dari berbagai hasil studi dan laporan, yang dikontruksi menjadi karakteristik akuisisi lahan, faktor penyebabnya, dampak yang dihasilkan, serta urgensi solusi untuk menekan penyebarannya. Hasil kajian menunjukan bahwa di Indonesia hal ini juga berlangsung, dan telah mulai memperlihatkan berbagai dampak yang kurang sejalan dengan visi dan misi pembangunan pertanian nasional, terutama ancamannya terhadap pencapaian ketahanan pangan dan kesejahteraan petani. Ke depan, semestinya fenomena akuisisi lahan harus dijadikan sebagai agenda terbuka dan dicarikan solusinya dengan mengintegrasikan dengan perencanaan reforma agraria.